Yaquis of Southern California in-between the US-Mexico border - Aracely RIVERA COHEN (E-REA)
This article seeks to examine the “in-betweenness” of the Yaqui Nation on both sides of the US-Mexico border: the Yaqui Nation of Southern California (YNSC) and the Yaqui Nation of the Yaqui River. It presents the in-between amid the “new” and the traditional ceremonial and migration practices of the Yaqui diaspora in California. This paper concludes that the Yaquis of Southern California case is a demonstration of the collective transnational, cultural-ethnic and political practices of the Yaqui peoples. These practices are evidence of what Homi Bhabha called cultural hybridity. The YNSC case is the “beyond” culture that negotiates, redefines, and questions ethnic communities.